The effect of Niobium oxide as a promoter on -Al2O3 based oxygen carrier for chemical looping combustion - et.al, Nur Adibah Mohd Ghazalia (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Chemical looping combustion (CLC) is known as a low-cost strategy for the capture of carbon dioxide for fuel combustion. In CLC process, oxygen carriers (OCs) are the cornerstone and play a vital role in defining reaction process. The aim of the present work was to investigate the potential of niobium (Nb) as a promoter on the -Al2O3 and its behavior as an oxygen carrier for chemical looping combustion process. In this work, the Nb loading was varied between 5 – 15 wt. %. Their behavior in CLC was analyzed by TPR, TPO, SEM and TGA. From the TPR results, the reduction temperature for 5 wt.%, 10 wt.% and 15 wt.% Nb loading were 560 ℃, 529 ℃ and 545 ℃, respectively which indicated that reduction reaction occurs around 500 ℃ and above. SEM analysis showed that increasing of Nb loading resulted in some agglomeration and thus lowering the ability of metal oxide to gain and release oxygen. The redox characteristics were carried out using TGA with 5% CH4/N2 was used as the reducing gas, while air was used as oxidizing gas. The highest oxygen transfer capacity was 3.0% which is presented by 5 wt.% of Nb loading. Since the addition of Nb successfully improved the oxygen transport capacity, it can be concluded that Nb is the potential candidate for oxygen carrier in CLC.